2022
DOI: 10.1111/echo.15485
|View full text |Cite
|
Sign up to set email alerts
|

Could premature ventricular contractions lead to atrial remodeling?

Abstract: Background: Premature ventricular contraction (PVC) is a frequent kind of arrhythmia that affects around 1% of the general population. While PVC most frequently impairs ventricular function in structurally normal heart, retrograde ventriculo-atrial conduction can occur in people with PVC. These retrograde atrial activations may mimic pulmonary vein-derived atrial ectopies. As a result, PVC may raise the risk of atrial fibrillation (AF) by retrograde ventriculo-atrial conduction. The Four-Dimensional Automated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Keles et al ( 22 ) found that patients who had premature ventricular contraction showed a significant decrease in the LAS compared with those in the control group. Ventricular arrhythmias can lead to atrial and ventricular remodeling, and 4D-LAQ can quantitatively detect these changes at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…Keles et al ( 22 ) found that patients who had premature ventricular contraction showed a significant decrease in the LAS compared with those in the control group. Ventricular arrhythmias can lead to atrial and ventricular remodeling, and 4D-LAQ can quantitatively detect these changes at an early stage.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with frequent premature ventricular complex (PVC), Sre decreased significantly regardless of age ( P < .001) ( Table 1 ). 3 …”
mentioning
confidence: 99%
“…We demonstrated that the longitudinal and circumferential strain values of LA were considerably lower in PVC patients ( P < .001). 4 …”
mentioning
confidence: 99%